Odległość ekonomiczna w modelowaniu zjawisk przestrzennych z wykorzystaniem modelu grawitacji; Economic distance in modeling spatial phenomena with the application of gravity model - Michal Bernard Pietrzak; Justyna Wilk (Institute of Economic Research (IER), 2014)
– The paper discusses the issue of an economic distance and its significance in modeling phenomena occurring in regional space. Economic distances between regions were deter-mined and their influence on internal migration flows in Poland in the period 2000-2010 was examined. The period before Poland's accession to the EU, as well as two periods re-ferring to the changes in economic trend and the intensity of domestic migrations, was considered. The economic distance is one of the most significant determinants of internal migration flows. In comparison to the geographical distance, it undergoes changes in time and space. Furthermore it affects the intensity of flows between regions in the opposite di-rection. Higher economic distance results in more intensive interactions between regions.
Keywords: C21; J11; O11; O15; R11; R23; 330; economic distance; regional development; gravity model; internal migrations